2019
DOI: 10.1115/1.4044392
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Thermofluid Performance of Fin-and-Tube Heat Transfer Surface Using Rectangular Winglets

Abstract: This paper numerically investigates the heat transfer enhancement using rectangular winglet pairs in a fin-and-tube type heat transfer surface having five inline rows of tubes. The influence of number of winglets, attack angles of the winglets, and their location has been analyzed under laminar flow conditions with Reynolds number ranging 400–1500. To account for the combined effect of heat transfer enhancement and pressure drop penalty, an enhancement factor is also discussed by changing the winglet pair's nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Arora et al (2015) and Sarangi and Mishra (2017) respectively used the delta and Rectangular winglet pairs in "commonflow-up" arrangement with inline tube orientation in a fin-and-tube heat exchanger to investigate the optimum winglet locations. Sarangi et al (2019) extended their research to five inline tubes supported with plain rectangular winglets and found out optimum winglet locations for highest enhancement factor. Similar investigations were performed by Naik and Tiwary (2018) with "common flow down" winglet orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Arora et al (2015) and Sarangi and Mishra (2017) respectively used the delta and Rectangular winglet pairs in "commonflow-up" arrangement with inline tube orientation in a fin-and-tube heat exchanger to investigate the optimum winglet locations. Sarangi et al (2019) extended their research to five inline tubes supported with plain rectangular winglets and found out optimum winglet locations for highest enhancement factor. Similar investigations were performed by Naik and Tiwary (2018) with "common flow down" winglet orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The application of VGs is developed as an effective technique to control the secondary flow strength. Lots of work has been done in heightening the fin side heat transfer coefficient by using VGs on fin surfaces [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For finned circular tube heat exchangers, the key point to improve the fin side thermal performance is to strengthen the local heat transfer ability and lessen the size of tube wake region, which are very closely dependent on the location and geometry parameters of VGs.…”
Section: Introductionmentioning
confidence: 99%
“…As for the rectangular VGs, Naik et al [11] found that the location of VGs is the dominant factor to affect the fin side thermal performance, and a superior heat transfer augmentation can be gained by placing rectangular VGs to the upstream of each tube. Sarangi et al [12] studied the enhanced heat transfer of an exchanger containing five inline rows of tubes and parallel fins with rectangular VGs; they reported that the number of VGs and their positional parameters have major effects on thermal performance. Gorji [13] investigated the influence of the longitudinal location of rectangular winglet pairs on thermal-hydraulic characteristics at different Re.…”
Section: Introductionmentioning
confidence: 99%
“…Arora et al [25] performed a similar type of investigation with three rows of inline tubes and twenty possible locations of VGs. Sarangi and Mishra [26] and Sarangi et al [27] carried out numerical simulations with rectangular VGs in a FTHX and determined the optimum winglet number, winglet attack angle, and winglet locations (stream wise and span wise). They also examined the influence of wavy nature of the rectangular winglets in FTHX [28].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the VGs are positioned with a heretofore-unused combination-'split winglet pairs over the elliptical tubes' for enhancement in heat transfer with lower pressure drop penalty. The full-length winglet used in the previous literature [27] is split into equal parts in the present study and their optimum locations have been investigated to provide greater control of thermal mixing behind the tubes.…”
Section: Introductionmentioning
confidence: 99%